A path analysis of diagnosis of employee job performance: Implications of the education office - Soeparlan Kasyadi; Virgana Virgana (Journal of Education and Learning (EduLearn), 2021)
The performance of education office organizations was influenced by the behavior of its employees. This study aimed to determine the direct and indirect influence of organizational culture, leadership style, personality, and organizational justice towards the job performance of the employee education office in Jakarta. Research samples were 221 employees of the Jakarta Education Office. Data collection using questioner with the Likert scale, The results of the research there was a direct influence of leadership style towards organizational justice; Organizational culture on organizational justice; Personality towards organizational justice; Leadership style on job performance; Organizational culture towards job performance; Personality towards job performance, then organizational justice towards job performance, and personality through organizational justice towards job performance. It was concluded that the level of job performance was influenced by variations in leadership style, organizational culture, personality, and organizational justice.